Answer:
1000. 100x10=1000 100+100+100+100+100+100+100+100+100+100=1000
100/1000=1/10
Step-by-step explanation:
Answer:-43 + 9x = 0
Step-by-step explanation:Simplifying
9x + -43 = 0
Reorder the terms:
-43 + 9x = 0
Solving
-43 + 9x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '43' to each side of the equation.
-43 + 43 + 9x = 0 + 43
Combine like terms: -43 + 43 = 0
0 + 9x = 0 + 43
9x = 0 + 43
Combine like terms: 0 + 43 = 43
9x = 43
Divide each side by '9'.
x = 4.777777778
Simplifying
x = 4.777777778
Answer:
36
Step-by-step explanation:
because square of term on LHS = square of term on RHS
if 5 - 3y = 6
then (5 - 3y)² = 36
Answer:
Positive.
Step-by-step explanation:
Negative to a even power becomes positive